The Integration of Chinese Culture Teaching in High Schools in Brazzaville, Congo: An Exploration from Methods to Curriculum Development - Freud Savinien Ngatseke Mampola (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
This study aims to incorporate Chinese culture teaching into Brazzaville high schools' curriculum to enhance China-Congo bilateral relations. Despite progress in Chinese language education there, Chinese culture education has clear shortcomings. Qualitative and exploratory methods were used. Data was collected via interviews with school personnel, student questionnaires, and classroom observations, along with in-depth case analyses of institutions with cultural initiatives. The findings revealed significant challenges: insufficient teacher training in cultural education, a lack of teaching resources, and limited access for students to Chinese culture. However, practical activities like embroidery workshops, kung-fu demonstrations, and costume exhibitions had great effects. They boosted students' interest and deepened their cultural understanding. Integrating such activities into the curriculum is crucial for a more engaging learning experience. Strategic planning, including building a fitting integration framework and providing teacher training, is needed. Based on the results, suggestions for administrators and policymakers were given, stressing more investment in teacher training and resources, and promoting cooperation with Chinese institutions. Future research can assess long-term impacts and explore exchange opportunities. This study endeavors to offer practical strategies to improve Chinese culture teaching quality in Brazzaville high schools.